On the prediction and monitoring of tungsten prompt redeposition in tokamak divertors. (June 2021) - Guterl, J.; Bykov, I.; Ding, R.; Snyder, P.
Abstract: As net erosion of tungsten plasma-facing components in tokamak divertors is strongly reduced by tungsten prompt redeposition, predicting and monitoring tungsten prompt redeposition is crucial to estimate the lifetime of tungsten PFCs and the source of tungsten impurities in tokamak divertors. To that end, a theoretical and numerical analysis of tungsten prompt redeposition near divertor targets is presented. It is shown that the reduction of the Larmor radius of tungsten impurities due to multiple ionizations during the first gyro-orbit of those impurities does not significantly lower tungsten prompt redeposition, as the sheath electric field is much stronger than the Lorentz force in the sheath region because of the large inertia of tungsten particles. As a consequence, only tungsten impurities which are ionized near or beyond the sheath entrance avoid prompt redeposition. Tungsten prompt redeposition is therefore mainly governed by the ratio of the ionization mean-free path of sputtered neutral tungsten particles over the sheath width. This governing parameter has similar values for divertor plasma conditions in DIII-D experiments and in plasma conditions expected in the far-SOL of the ITER divertor, indicating that investigations of tungsten erosion in smaller devices like DIII-D are relevant for future fusion reactors like ITER. Furthermore, this governing parameter scales linearly with the magnetic field strength. Tungsten net erosion in the divertor region might thus significantly increase in fusion devices operating at high magnetic field. It is also observed that the fraction of tungsten impurities which promptly redeposit is only correlated to the fraction of impurities in the highest charge state reached during the first gyro-orbit. As a consequence, in-situ monitoring of tungsten prompt redeposition in divertors requires monitoring photon emissions associated with the ionizations of tungsten impurities in charge states Z > 2 +, typically W 3 +, W 4 + and W 5 + for plasma conditions expected in the far-SOL of the ITER divertor. Highlights: The reduction of the Larmor radius of tungsten impurities due to the multiple ionizations of those impurities during their first gyro-orbit does not significantly lower tungsten prompt redeposition because of the large inertia of tungsten particles. only tungsten neutral impurities which are ionized near or beyond the sheath entrance avoid prompt redeposition. Tungsten prompt redeposition is mainly governed by the ratio of the ionization mean-free path of sputtered neutral tungsten particles over the sheath width. This governing parameter has similar values for divertor plasma conditions in DIII-D experiments and expected in ITER far-SOL. The governing parameter of tungsten prompt scales linearly with the magnetic field strength, such the net erosion of tungsten in the divertor region might significantly increase in fusion devices operating at high magnetic field. In-situ monitoring of the prompt redeposition of tungsten impurities in divertors requires monitoring photon emissions associated with the ionizations of tungsten impurities in charge states Z > 2+, typically W3+, W4+ and W5+ for ITER.